POSITION OF FORENSIC PSYCHOLOGY IN DETERMINING THE MENTAL HEALTH OF CRIMINAL OFFENDERS - Dirkareshza, Nada Prima; Bakhtiar, Handar Subhandi (Zhata Institut, 2025)
Forensic Psychology contributes to interpreting how psychological factors can influence a criminal act because Forensic Psychology has a crucial role in assessing the criminal responsibility of a perpetrator. The purpose of this study is to analyze how the results of forensic psychological examinations are used in the process of proving criminal cases and to what extent these results influence the judge's decision in determining the defendant's criminal responsibility. The research method used is a normative legal approach, by examining the provisions of the Criminal Code, the Criminal Procedure Code, and other related regulations, and supported by a case approach to court decisions involving perpetrators with indications of mental disorders. The position of forensic psychological examination results in the criminal law evidence system in Indonesia is in an important position, but is not yet fully strong normatively. The results of Forensic Psychological examinations have a significant influence on the determination of criminal responsibility by the judge, although their nature is not absolutely binding. The testimony of Forensic Psychological experts is one of the important considerations in determining whether or not there is an element of fault in the perpetrator, especially in the context of the principle of geen straf zonder schuld (no crime without fault).